Partnerships for sustainability in contemporary global governance pathways to effectiveness - Andonova, Liliana B.; Faul, Moira V.; Piselli, Dario (London Routledge, 2022)
Partnerships for Sustainability in Contemporary Global Governance investigates the goals, ideals, and realities of sustainability partnerships and offers a theoretical framework to help disentangle the multiple and interrelated pathways that shape their effectiveness.

Partnerships are ubiquitous in research and policy discussions about sustainability and are important governance instruments for the provision of public goods. While partnerships promise a great deal, there is little clarity as to what they deliver. If partnerships are to break free from this paradox, more nuance and rigor are required for understanding and assessing their actual effects. This volume applies its original framework to diverse empirical cases and could be extended both to broader data sets and case studies of partnerships. The dual contribution of this volume, theoretical and empirical, holds promise for a more thorough and innovative understanding of the pathways to partnership effectiveness and the conditions that can shape their performance. The broad range of case studies and cross-cutting analyses suggest important practical implications for the design of new partnerships and the updating of existing initiatives.

This interdisciplinary book will be of great interest to researchers, students, and practitioners within international relations, political science, sociology, environmental studies and global studies, as well as the growing number of scholars in public policy, global health and organizational and business studies who are keen to gain a deeper understanding of the pathways and mechanisms that influence the outcomes and effectiveness of cross-sector collaboration and transnational governance more broadly.
Part I. What Are Partnerships and How to Know their Effects? -- 1 The effectiveness of partnerships : theoretical framework / Liliana B. Andonova and Moira V. Faul -- Part II. Thematic Case Studies -- 2 Governing biodiversity and clean energy with global partners / Liliana B. Andonova and Dario Piselli -- 3 Protecting the Amazon and its people : the role of civil society in the local effectiveness of transnational partnerships / Livio Silva-Muller and Moira V. Faul -- 4 Brokering private action for sustainable development : the role of the World Bank / Axel Michaelowa, Katharina Michaelowa and Liliana B. Andonova -- 5 Advancing innovation and access to medicines : the achievements and unrealized potential of the product development partnership model / Marcela Fogaca Vieira, Ryan Kimmitt, Danielle Navarro, Anna Bezruki and Suerie Moon -- 6 Sustaining partnerships : the global polio eradication initiative case / Mara Pillinger -- 7 Founding the Global Partnership to End Violence Against Children : opportunities and challenges on the road to effectiveness / Susan L. Bissell and David Steven -- Part III. Crosscutting Themes -- 8 Partnerships under pressure : lessons on adaptation and overcoming challenges / Amanda Sardonis and Henry Lee -- 9 Effectiveness of transnational partnership regimes in long-term resource revenue management / Jamie Fraser and Gilles Carbonnier -- 10 Faultlines within sectors in partnership executive boards / Moira V. Faul and Younes Boulanguiem -- Part IV. Conclusion -- 11 Conclusion / Liliana B. Andonova, Moira V. Faul and Dario Piselli.
Includes bibliographical references and index.
Keywords: International cooperation; Environmental protection -- International cooperation; Sustainable development -- International cooperation; World health -- International cooperation; Children -- Violence against -- Prevention -- International cooperation